B cell autoimmunity and bone damage in rheumatoid arthritis - S. Bugatti; L. Bogliolo; C. Montecucco; A. Manzo (PAGEPress Publications, 2016)
Rheumatoid arthritis (RA) is a chronic immune-inflammatory disease associated with significant bone damage. Pathological bone remodeling in RA is primarily driven by persistent inflammation. Indeed, pro-inflammatory cytokines stimulate the differentiation of bone-resorbing osteoclasts and, in parallel, suppress osteoblast function, resulting in net loss of bone. Abating disease activity thus remains the major goal of any treatment strategy in patients with RA. Autoantibody-positive patients, however, often show a rapidly progressive destructive course of the disease, disproportionate to the level of inflammation. The epidemiological association between RA-specific autoantibodies, in particular anti-citrullinated protein autoantibodies, and poor structural outcomes has recently found mechanistic explanation in the multiple roles that B cells play in bone remodeling. In this review, we will summarize the substantial progress that has been made in deciphering how B cells and autoantibodies negatively impact on bone in the course of RA, through both inflammation-dependent and independent mechanisms.